German and Scandinavian Protestantism, 1700-1918 - Hope, Nicholas (Oxford history of the Christian Church., 1995)
Dealing with the early modern period from 1700 right through to the end of the First World War, and the beginning of a radically altered Europe, this is a full history of the Lutheran church in Germany and Scandinavia.